Research on mechanical performance of industrial polypropylene biaxial geogrid. (July 2021) - Ren, Xinbo; Zhao, Xinhai; Zheng, Chao; Song, Libin; Yang, Xiaoling; Liu, Zhenzhen
Abstract: Biaxial plastic geogrid is a polymer mesh formed by biaxial stretching. When making biaxial plastic geogrids, generally, the polymer sheet made by extrusion is pre-punched first, and then the biaxial stretching is carried out at an appropriate temperature. Different sizes of pre-punched holes will affect the subsequent stretching process, thereby changing the mechanical properties of the grid. In this study, geogrids made of different pre-punched diamond-shaped hole plates were subjected to room temperature tensile test. Influence of diameter-to-distance ratio and the percentage difference of longitudinal and transverse spacing on the mechanical properties of biaxial geogrids were studied experimentally and numerically. The results show that when the holes are appropriately small and the longitudinal spacing between the holes is slightly larger than the transverse spacing, the mechanical properties of the grid can be the best, and transverse stretching process will affect the longitudinal ribs in different aspects. Highlights: The mechanical properties of biaxial geogrid are related to the parameters of pre-punching holes. The shape and stress-strain law of biaxial plastic geogrid can be analyzed by numerical simulation. Transverse stretching process will affect the mechanical properties of longitudinal ribs.